Determinants of perceptions of organizational support and job satisfaction on employee performance - Magita Magita; Sri Anjarwati; Dedy Kurniawan (Sean Institute, 2024)
Human resources are an element in carrying out all activities of a company. Organizations expect employee performance to be as high as possible to achieve organizational excellence and compete in the corporate world. A company's performance can run well if the performance of its employees supports it. The research aims to analyze the influence of perceived organizational support and job satisfaction on employee performance at PT. XYZ. This type of research is quantitative using the causality method—population of PT employees. XYZ has 32 employees as respondents. The sampling technique is a census, which makes all population members into research samples. The research instrument used was a questionnaire with a Likert scale. The data analysis used is a structural equation model with Smartpls software. This research examines perceived organizational support and job satisfaction determinants, which influence employee performance at PT. XYZ Jakarta, original, is the object of research and analysis using the Smartpls tool. The research results of perceptions of organizational support are not significant on employee performance, and job satisfaction influences employee performance at PT. XYZ Jakarta.